2006
DOI: 10.1159/000090676
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Lower Apolipoprotein A-I in Alzheimer’s Disease

Abstract: Many researches have been trying to find the potential biomarkers for Alzheimer’s disease (AD). We hereby used the proteomics method to search for protein expression differences in the serum between AD patients and controls. We enrolled 59 AD patients and 74 age- and sex-matched controls in this study. Ten AD patients and 10 controls were selected for proteomic analysis. Apolipoprotein A-I (ApoA-I) was found to have a lower expression in the AD group by a proteomics two-dimensional gel electrophoresis study. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 62 publications
7
50
0
2
Order By: Relevance
“…Besides the simultaneous use of high concentrations of total or phosphorylated tau combined with reduced concentrations of A ␤ 42 to predict conversion of patients with mild cognitive impairment (MCI) to AD [8] , several techniques including proteomics allowed us to identify other proteins involved in A ␤ metabolism and vascular physiology as biomarkers for AD [9] . Thus a decrease in apolipoprotein A-I (APOA1) levels in AD patients was consistently reported [7,[10][11][12] .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Besides the simultaneous use of high concentrations of total or phosphorylated tau combined with reduced concentrations of A ␤ 42 to predict conversion of patients with mild cognitive impairment (MCI) to AD [8] , several techniques including proteomics allowed us to identify other proteins involved in A ␤ metabolism and vascular physiology as biomarkers for AD [9] . Thus a decrease in apolipoprotein A-I (APOA1) levels in AD patients was consistently reported [7,[10][11][12] .…”
Section: Introductionmentioning
confidence: 78%
“…That is why extensive searches for peripheral biochemical markers for AD are still conducted. The results show alterations for multiple proteins in cerebrospinal fluid samples and in serum [7] . Besides the simultaneous use of high concentrations of total or phosphorylated tau combined with reduced concentrations of A ␤ 42 to predict conversion of patients with mild cognitive impairment (MCI) to AD [8] , several techniques including proteomics allowed us to identify other proteins involved in A ␤ metabolism and vascular physiology as biomarkers for AD [9] .…”
Section: Introductionmentioning
confidence: 88%
“…In sharp contrast to apoE, apoAI is not synthesized in the CNS and its presence in CSF indicates transit across the blood-brain barrier (124). Polymorphisms in the gene that encodes apoAI have been correlated with AD dementia or all-cause dementia (19, 20); plasma and serum apoAI levels are decreased in patients with AD dementia (2224); and serum levels of apoAI have been associated inversely with risk of AD dementia (21). Furthermore, recent studies have shown the lack of apoAI increases cerebral amyloid angiopathy and memory deficits of AD dementia (125), and increasing plasma apoAI levels provides cognitive and neuropathological benefits in animal models of AD dementia (126).…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases [36,37], blepharitis [38], Down syndrome [39], diabetic nephropathy [40] have also been investigated by means of 2Dgel analysis of sera Many potential serum markers were identified, but protein serum level seems to change dramatically only at an advanced disease stage.…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%